Facile synthesis of economical feasible fly ash–based zeolite–supported nano zerovalent iron and nickel bimetallic composite for the potential removal of heavy metals from industrial effluents. (March 2021) - Angaru, Ganesh Kumar Reddy; Choi, Yu-Lim; Lingamdinne, Lakshmi Prasanna; Choi, Jong-Soo; Kim, Dong-Su; Koduru, Janardhan Reddy; Yang, Jae-Kyu; Chang, Yoon-Young
Abstract: Heavy metals contamination of water is one of the environmental issue globally. Thus prepared fly ash–based zeolite (FZA)–supported nano zerovalent iron and nickel (nZVI/Ni@FZA) bimetallic composite from low-cost fly ash waste for the potential treatment of anion (Cr(VI) and cation Cu(II)) heavy metals from industrial effluents at pH 3 and 5, respectively in this study. The systematic interaction between FZA and nZVI/Ni and the adsorptive removal mechanism was studied. The mean surface area of the nZVI/Ni@FZA (154.11 m 2 /g) was much greater than that of the FZA (46.6 m 2 /g) and nZVI (4.76 m 2 /g) independently, as determined by BET-N2 measurements. The effect of influence factors on the removal of Cr(VI) and Cu(II) by nZVI/Ni@FZA, such as pH effect, initial concentration effect, time effect, temperature effect, coexisting metals, and ionic strength, and cumulative loading ability, were discussed. The maximum adsorption capacity of nZVI/Ni@FZA was 48.31 mg/g and 147.06 mg/g towards Cr(VI) and Cu(II), respectively. These were higher than those of nZVI@FZA and FZA. It demonstrated that Ni could play an important role in enhancing the reduction ability of nZVI. Furthermore, isothermal and kinetic results revealed that both heavy metal adsorption processes were rate limiting monolayer Langmuir adsorption on homogeneous surfaces. Thermodynamic results suggested that the adsorptive removal of metal ions was endothermic with spontaneity. The applicability of nZVI/Ni@FZA on real industrial wastewater treatment results demonstrate that the concentration of heavy metals were removed under the acceptable standard levels. Further the adsorption capacity of nZVI/Ni@FZA was higher than the nZVI@FZA and FZA. The overall results demonstrated that nZVI/Ni@FZA was a promising, efficient, and economically feasible sorbent for potential wastewater treatment. Moreover this is first report on the preparation nZVI/Ni@FZA bimetallic composite. Highlights: First report on the preparation and use of low-cost fly ash based zeolite-A-nZVI/Ni. The prepared material well characterized using advanced techniques. nZVI/Ni@FZA showed high removal efficiency for Cu(II) and Cr(VI) than zeolite. The surface mechanism was well explained. It was well applied for real industrial wastewater treatment.